2018
DOI: 10.1186/s40780-018-0105-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist counseling on reducing instances of adverse events that can affect the quality of life of chemotherapy outpatients with breast Cancer

Abstract: BackgroundIn recent years, cancer chemotherapy is being conducted at outpatient clinics, wherein pharmacists are involved with patient guidance and management of adverse events as experts in medication therapy. Therefore, we clarified the influence of interventions by pharmacists during counseling of patients with cancer on patients’ quality of life.MethodsTo determine this influence, we conducted a survey to assess the quality of life of 39 patients with breast cancer who underwent their initial course of out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…16,17 While less often studied in oncology, pharmacist interventions were linked with improvement in patient-reported quality of life scores in patients with breast cancer. 18 The objective of this study was to quantify the effect of a smart pill bottle (SPB) and targeted pharmacist interventions when notified of missed uncapping events on medication adherence in MM patients taking oral lenalidomide. Lenalidomide was chosen because it is an oral oncology medication patients take from home, with a complicated timeon time-off cycle dosing regimen, and it has a high-touch REMS program, providing multiple points of contact between…”
Section: Study Proceduresmentioning
confidence: 99%
“…16,17 While less often studied in oncology, pharmacist interventions were linked with improvement in patient-reported quality of life scores in patients with breast cancer. 18 The objective of this study was to quantify the effect of a smart pill bottle (SPB) and targeted pharmacist interventions when notified of missed uncapping events on medication adherence in MM patients taking oral lenalidomide. Lenalidomide was chosen because it is an oral oncology medication patients take from home, with a complicated timeon time-off cycle dosing regimen, and it has a high-touch REMS program, providing multiple points of contact between…”
Section: Study Proceduresmentioning
confidence: 99%
“…Pharmacists can also screen for adherence to anticancer therapies, side effects, drug-drug, drug-food, and drug-herb interactions [ 33 – 36 ]. Tanaka et al reported that counseling by pharmacists increased the quality of life and reduced the side effects associated with chemotherapy among patients with breast cancer [ 37 ]. A previous study showed that patients with breast cancer who received counseling and education with regard to their treatment and side effects by pharmacists had less anxiety and better psychological outcomes compared to patients who did not receive counseling and education [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists can improve chemotherapy breast cancer patients' QOL regarding malaise and nausea by providing personal counseling before the medical examinations. In addition to the attending physician and nurses, pharmacists can also partially alleviate malaise through active intervention that involves patient counseling and guidance [452]. It is worth mentioning that clinical pharmacists are well accepted as patient medication educator and psychological consultant.…”
Section: C) Breast Cancermentioning
confidence: 99%